خانقاہ سلطانیہ کی سماجی خدمات کا تحقیقی جائزہ: An Analytical Study of the Social Services of Khānqāh Sultānia (Al-Qamar, 2021)
Islam is not only combination of rituals like Slāt and Sawm (fast)but it equally emphasizes on the importance of social services. We find many examples in the teaching of the Holy Quran and Hadīth where the rights of people have been stressed. The life of Holy prophet (PHUH) is a role model in this regard. Sufis have adopted the social services as basic subject of their training course. The shrine of Sultānia which is a famous shrine of Mujadidia Sufi order has this basic tradition. This shrine also promotes the love of humanity along with the remembrance of the Allah. The Sufi of this order practically help the people by constricting the noises for needy, providing the medical treatment to the poor patients and establishing schools for the community. They help those people who lived in far flung areas where there was no presence of government institutions.
Keywords: Khānqāh Sultānia; Social Services; Love; Peace; Humanity; Islam; Sufism; Sufis; Harmony